Primary Pulmonary Carcinoid Tumor: A Long-term Single Institution Experience. (January 2018) - Herde, Ryan F.; Kokeny, Kristine E.; Reddy, Chakravarthy B.; Akerley, Wallace L.; Hu, Nan; Boltax, Jonathan P.; Hitchcock, Ying J.
Abstract : Objectives: Primary carcinoid tumors of the lung are rare tumors which comprise approximately 0.5% to 5% of all lung malignancies in adults and roughly 20% to 30% of all carcinoid tumors. The purpose of this retrospective, descriptive study was to describe the incidence, characteristics, and outcomes of patients treated for primary pulmonary carcinoid tumor at a single institution. Materials and Methods: All patients with a diagnosis of primary pulmonary carcinoid tumor treated from 1989 to 2009 were reviewed. Data collected included demographics, pathology, tobacco use, clinical presentation, tumor location, tumor spread, treatment, and survival. Results: There were 59 cases of pulmonary carcinoid tumors: 47 typical (80%) and 12 atypical (20%). All but 4 patients underwent surgery, including 54 (92%) lung-sparing resections and 1 pneumonectomy. Five of 55 patients received concurrent adjuvant chemoradiation therapy; 4 patients with atypical and 1 with typical histology. Three additional patients with atypical carcinoid were treated only with adjuvant radiotherapy, palliative radiotherapy, or palliative chemotherapy, respectively. The Kaplan-Meier 5- and 10-year overall survivals were both 80% within the entire population. In the 88% of patients who achieved complete remission, disease-free survival was 98%. A review of a large series from the literature is also presented. Conclusions: Surgical resection was primary and adequate therapy for most typical carcinoid tumors with high overall survival and disease-free survival. Adjuvant chemotherapy or radiotherapy might be considered for patients with atypical carcinoid tumors who present with adverse pathologic findings.